Dressmaking : the easy guide - Rhiannon, Helen (Search Press, 2023)
"From just 5 basic patterns elements, learn to mix and match these elements to create over 80 different bespoke garments that are unique to you. With full-size patterns to cater for dress sizes 2 to 42"--